Profil Cuaca dan Parameter Nisbah Bowen di Areal Persawahan Kabupaten Indramayu Saat Periode Kering Musim Tanam II - Roberto I. C. O. Taolin; Impron Impron; Rini Hidayati; Bregas Budianto (Fakultas Pertanian, Universitas Timor, 2017)
The objectives of this experiment were to study the weather profile and parameters of Bowen ratio in the Indramayu rice field area during a dry period season of planting II. Results showed that daily weather fluctuations and Bowen ratio parameters were in line with incoming net radiation of each element. Temperature, dry bulb temperature gradient, wind speed, soil heat flux, and latent heat flux increased at midday and decreased in the early afternoon, whereas wet bulb temperature gradient, humidity, and air pressure were decreased at midday and increased at afternoon. Diurnal variation of net radiation ranged from -47 to 487 Wm-2 with the mean was 241 Wm-2. Mean, maximum and minimum temperatures were 28.3 of 31.5oC, and 20.5oC, respectively. Mean of relative humidity was 66% with the range was 52% to 80%, and mean of air pressure was 101 kPa. Soil heat flux ranged from 10.3 to 19.3 Wm-2 with the mean was 8.1 Wm-2. Mean and range of Bowen ratio were 0.16 and -0.76 to 0.65, accordingly. Mean and range of latent heat flux were 172.9 Wm-2 and -85.3 to 392.3 Wm-2. Surface incoming net radiation during the measurement period was constantly ranged from 183 to 268 Wm-2 with the mean was 231 Wm-2. Mean, maximum and minimum temperatures were 29.4 of 35.5oC, and 20oC, respectively. Mean of relative humidity was 59% with the range was 45% to 67%, and mean of air pressure was 101 kPa. Wind velocity was 0.9 ms-1 and its flow direction was mostly from the Southeast (138.4o). Soil heat flux was high at the end of measurement period; ranged from 4.7 to 14.6 Wm-2 with the mean was 7.9 Wm-2. Mean and range of Bowen ratio were 0.10 and 0.02 to 0.22, accordingly. Latent heat flux value was directly proportional to incoming net radiation, ranged from 134.4 to 226.5 Wm-2 and the mean was 184 Wm-2.